Six-year follow-up of maxillary anterior rehabilitation with forced orthodontic extrusion: Achieving esthetic excellence with a multidisciplinary approach - Barros, Luiz Antônio Borelli [UNESP]; De Almeida Cardoso, Maurício; De Avila, Érica Dorigatti [UNESP]; De Molon, Rafael Scaf [UNESP]; Siqueira, Danilo Furquim; Mollo-Junior, Francisco de Assis [UNESP]; Capelloza Filho, Leopoldino (Elsevier, 2013)
Orthodontic extrusion with multidisciplinary treatment can provide predictable outcomes in selected situations, reducing the costs and the adaptation times of gingival tissues after implant integration. Forced orthodontic extrusion is strongly related to interactions of teeth with their supportive periodontal tissues. This article reports a case of orthodontic extrusion of the maxillary incisors for later implant rehabilitation in a patient with periodontal disease. Slow forces were applied for 14 months. After this time, the teeth were extracted, and the implants were placed on the same day. Also in the same session, the provisional crown was fabricated for restoration of the anterior maxillary interdental papillae loss and for gingival contouring. Clinical and radiographic examinations at the 6-year follow-up showed successful tooth replacement and an improved esthetic appearance achieved by this multidisciplinary treatment. The decision to perform orthodontic extrusion for implant placement in adult patients should be multidisciplinary. Copyright © 2013 by the American Association of Orthodontists.